2016
DOI: 10.1021/acs.jproteome.6b00566
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomic Perturbations in Lung, Kidney, and Liver Tissues of p53 Knockout Mice Analyzed by Nanoflow UPLC-ESI-MS/MS

Abstract: Lipids are important signaling molecules regulating biological processes under normal and diseased conditions. Although p53 mutation is well-known for causing cancer, the relationship between p53-related tumorigenesis and altered lipid profile is unclear. We profiled differences in lipid expressions in liver, lung, and kidney in p53 knockout (KO) mice by high-speed quantitative analysis of 320 lipids (399 species identified) using nanoflow ultrahigh performance liquid chromatography−tandem mass spectrometry (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Additionally, the two diacylglycerol (DAG) (16:0,16:0 and 18:2,20:1) and the six TAG (44:2, 44:2, 46:0, 50:0, 58:5, 58:8, and 58:9) were not altered in the Gas, but highly elevated in the Sol. When comparing the lipid species significantly altered in internal organs (the liver, kidney, and lung) in the p53 KO mice 13 , only five species listed in Table 2 (marked with *) increased in the internal organs: 18:0/18:0-PI, 18:0/20:5-PI, 44:2-TAG, and 50:0-TAG. While Cer is known to induce apoptosis, formation of hexosylceramide like MHC from Cer allows cells to escape ceramide-induced apoptosis 26 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the two diacylglycerol (DAG) (16:0,16:0 and 18:2,20:1) and the six TAG (44:2, 44:2, 46:0, 50:0, 58:5, 58:8, and 58:9) were not altered in the Gas, but highly elevated in the Sol. When comparing the lipid species significantly altered in internal organs (the liver, kidney, and lung) in the p53 KO mice 13 , only five species listed in Table 2 (marked with *) increased in the internal organs: 18:0/18:0-PI, 18:0/20:5-PI, 44:2-TAG, and 50:0-TAG. While Cer is known to induce apoptosis, formation of hexosylceramide like MHC from Cer allows cells to escape ceramide-induced apoptosis 26 .…”
Section: Resultsmentioning
confidence: 99%
“…Few studies showed the influence of p53 mutation on lipid profiles such as an observation in the change of unsaturated acyl chains of phospholipids (PLs) toward more saturated moieties in p53 knockout (KO) liver cells 10 , a decrease of acyl chain length of phosphatidylinositol (PI) by p53 mutation in pancreatic cancer 11 , and an increase of phosphatidylcholine (PC) levels in p53 KO colon cancer cell lines by magnetic resonance imaging (MRI) and spectroscopy (MRS) 12 . Most recently, we performed a series of lipidomic analyses of three internal organ tissues (the lung, kidney, and liver tissues) and three brain tissues (the cortex, hypothalamus, and hippocampus) derived from p53 KO mice using nanoflow liquid chromatography-electrospray ionization-tandem mass spectrometry (nLC-ESI-MS/MS) and demonstrated that p53 status altered lipid profiles in a tissue-specific manner 13, 14 . Since p53 is associated with the maintenance of mitochondrial functional properties in the skeletal muscle 15, 16 and dysfunctional utilisation of lipids in mitochondria is associated with muscle-related diseases such as diabetes, obesity, and sarcopenia 1720 , it is important to investigate the role of p53 in lipid metabolism of skeletal muscles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in this section we will focus only on quoting several reviews (Bhattacharya, ; Butovich, ; Colsch, Seyer, Boudah, & Junot, ; Gooley & Chua, ; Kolovou, Kolovou, & Mavrogeni, ; Touboul & Gaudin, ; Yang et al, ; Zhao, Cheng, Lin, & Wei, ) and on a selection of the most promising original research. Lipidomic analysis is primarily used to detect changes in the lipid profile of the brain (Gaudin et al, ; Proitsi et al, ; Zhang, Chen, Liang, & Zhang, ), kidney (Cifkova et al, ), blood (Surma et al, ), or liver (Park et al, ), but also other tissues and secretions of mammals, for example, horse semen (Wood, Scoggin, Ball, Troedsson, & Squires, ). In essence, the lipidomic analyses in humans are most commonly published in relation to various diseases or their prevention.…”
Section: Cyanobacteria and Algaementioning
confidence: 99%
“…As the available sample amount becomes a limiting factor, for example with small tissue sections from biobanks or small cell subpopulations, it is increasingly attractive to employ nanoflow chromatography [15][16][17] .…”
mentioning
confidence: 99%